THE EFFECTS OF THE TRAINING IN THE PREPARATION PERIOD ON THE DRIBBLING SPEED WITH FIFTEEN YEARS OLD FOOTBALL PLAYERS - Jovan Gardašević; Duško Bjelica (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2014)
Introduction: The main aim of the research was to identify a level of quantitative changes of the dribbling speed with fifteen years old football players under the influence of the programmed football training of a six weeks preparation period. Methods: According to the time orientation this was a longitudinal study with the aim to define in a two timely different points a quantitative changes of the dribbling speed under the influence of the programmed football training with fifteen years old football players under the influence of the programmed training process, which involved a summer preparation period and lasted forty-two days. The training programme covered forty-four training units. The research was made on a sample of 120 fifteen years old football players of cadet rank. For the assessment of ball handling the three tests were used: horizontal ball rebounding from a wall 20s, dribbling speed of the ball in slalom and juggling alternating with both feet in a square space of 1x1m. In the area of comparative statistics, we used discriminant parametric procedure t-test for big paired samples. Results: Based on the numerical values of the t-test it can be concluded that there are no statistically significant differences in all three variables to estimate the dribbling speed. This confirmed the hypothesis that the expected significant positive quantitative changes of situational-motor abilities influenced by the proposed model of training in preparation period with fifteen years old football players. Discussion: In this research the authors were guided by the fact that this kind of training program in preparation period, where dominates the situational model training is very effective in terms of raising the dribbling speed with fifteen years old, because the model that is used in this training period abounds in exercises in which dominates dribbling speed, in stright line and with changes in direction. The obtained results can be directed towards innovation plans and programs in the preparation period, and the adaptation of the same needs of the respective population. References: Bajramovic I, Talovic M, Alic H, Jeleskovic E (2008). Sport Mont, 15, 16, 17./VI, 104-9. Bjelica D (2003). The effect of football training on biomotor status of cadets in Montenegro, Ph.D. Thesis, Faculty of Sports and Physical Education of University of Belgrade. Bjelica D (2004). Sport Mont, 4/II, 58-71. Bjelica D (2005). Sport Mont, 8-9, 26-41. Michels R (2001). Teamcoaching: Der Weg zum erfolg durch Teambuilding, Bpf Versand-onli Verlag.